Prestasi Belajar dan Karakteristik Orang Tua: Studi Perbandingan Sekolah Menengah Atas Perkotaan-Pedesaan - Khusaini, Khusaini; Muvera, Muvera (Jurnal Pendidikan Ekonomi Undiksha, 2020)
Rural-urban gaps in development lead to disparities in income, poverty, and the disparity in education. This study intends to examine the differences in public senior high schools (SMA) in urban and rural areas. This comparisons were analyzed according to the characteristics of learning achievement, school conditions, and characteristics of teachers in rural and urban areas. Researchers set the school as the object of research, namely SMA Negeri 14 Tangerang Regency representing rural areas and SMA Negeri 7 Kota Tangerang Selatan representing urban areas. Atuthors used valid and reliable the research instruments. The target populations size were 7.206 students and terachers. The samples size were 100 students and 89 teachers with simple random sampling technique. The hypothesis test used Mann-Whitney U-test. The results showed that urban senior high school was more better than rural based on students achivement and parental characteristics, but the characteristics of teachers and school facilities did not differ significantly. This study contributed in providing policy input to local governments and rural schools to encourage improved learning achievement and pay attention to the situation of their parents.